Myocardial Infarction (MI) presenting as acute limb: an extremely rare presentation of MI - Aziz, Fahad (Pioneer Bioscience Publishing Company, 2010)
Acute embolic occlusion of the bilateral lower limbs from the left ventricular thrombus is an extremely rare medical condition that is not only limb threatening but also potentially life threatening. Several strategies are available but not even a single treatment modality is clearly the best. Here, we present an interesting case that presented with bilateral lower limb ischemia and was later found to have a big thrombus in the left ventricle as the source of the emboli.